Prevalence of musculoskeletal disorders among plastics industry workers Prevalência de distúrbios musculoesqueléticos em trabalhadores da indústria plástica - Rita de Cássia Pereira Fernandes; Fernando Martins Carvalho; Ada Ávila Assunção (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The prevalence of musculoskeletal disorders among workers in the plastics industry in Salvador, Bahia State, Brazil was estimated. Cases were defined by reported symptoms of pain in the previous 12 months, lasting more than a week or having monthly minimum frequency, which had given rise to restrictions at work or to seeking medical attention, or where respondents had a severity score greater than or equal to 3 (on a numerical scale of 0 to 5). A stratified proportional random sample of 577 workers was studied. The prevalence of musculoskeletal disorders, considering of all body segments, was 50.1%. The prevalence of musculoskeletal disorders was higher among women than among men at distal upper extremities (34.6% and 11.6% respectively) and also in the region of the neck, shoulder or upper part of the back (27.4% and 17.6% respectively). There was no difference between genders for the prevalence of lower back pain (21.2% and 21.4% respectively); 65% of cases in this region had reports of pain in the previous seven days. Due to the importance and prevalence of musculoskeletal disorders, it is necessary that their measurement in epidemiological studies be done properly. Estimou-se prevalência de distúrbio musculoesquelético em trabalhadores da indústria de plástico, em Salvador, Bahia, Brasil. Casos foram definidos pelo relato de sintomas de dor nos últimos 12 meses, com duração maior do que uma semana ou freqüência mínima mensal, que haviam determinado restrição ao trabalho ou procura médica, ou tinham gravidade maior ou igual a 3 (numa escala numérica de 0 a 5). Estudou-se uma amostra aleatória estratificada proporcional de 577 trabalhadores. A prevalência de distúrbio musculoesquelético, considerando todos os segmentos corporais, foi de 50,1%, sendo maior entre mulheres do que entre homens nas extremidades superiores distais (34,6% e 11,6%, respectivamente) e na região de pescoço, ombro ou parte alta do dorso (27,4% e 17,6%, respectivamente). Não houve diferença entre os sexos para a prevalência de lombalgia (21,2% e 21,4%, respectivamente) e 65% dos casos nesta região apresentaram dor nos últimos sete dias. Devido à grande importância e prevalência dos distúrbios musculoesqueléticos, é necessário que a sua mensuração seja feita adequadamente, em estudos epidemiológicos.